2021
DOI: 10.1016/j.isci.2021.102924
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen evolution catalysis by terminal molybdenum-oxo complexes

Abstract: Summary Stable complexes with terminal triply bound metal-oxygen bonds are usually not considered as valuable catalysts for the hydrogen evolution reaction (HER). We now report the preparation of three conceptually different (oxo)molybdenum(V) corroles for testing if proton-assisted 2-electron reduction will lead to hyper-reactive molybdenum(III) capable of converting protons to hydrogen gas. The upto 670 mV differences in the [(oxo)Mo(IV)] - /[(oxo)Mo(III)] −2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 52 publications
1
22
0
Order By: Relevance
“…The contracted and tri-(rather than di-) anionic N 4 coordination core of corroles induces unusual reactivity and stability at the low and high oxidation state, respectively. [40,41] The redox potentials of metallocorroles are easily tuned by the nature of substituents at the meso-C position and via selective postfunctionalization. [42,43] Moreover, metallocorroles are extremely stable towards hydrolysis, and show a much reduced tendency of forming inactive μ-oxo-bridged bis-iron complexes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The contracted and tri-(rather than di-) anionic N 4 coordination core of corroles induces unusual reactivity and stability at the low and high oxidation state, respectively. [40,41] The redox potentials of metallocorroles are easily tuned by the nature of substituents at the meso-C position and via selective postfunctionalization. [42,43] Moreover, metallocorroles are extremely stable towards hydrolysis, and show a much reduced tendency of forming inactive μ-oxo-bridged bis-iron complexes.…”
Section: Introductionmentioning
confidence: 99%
“…An exciting new family of Fe−N 4 electrocatalysts is the family of metallocorroles, which have already been used for electrocatalyzing both reduction (of protons, oxygen, and CO 2 ) [34–36] and oxidation (hydroxide and water) [37–39] half‐cell reactions. The contracted and tri‐ (rather than di‐) anionic N 4 coordination core of corroles induces unusual reactivity and stability at the low and high oxidation state, respectively [40,41] . The redox potentials of metallocorroles are easily tuned by the nature of substituents at the meso ‐C position and via selective postfunctionalization [42,43] .…”
Section: Introductionmentioning
confidence: 99%
“…35 The meso-CF 3 substituted molybdenum corrole displays more outstanding HER productivity and positive potential than the meso-C 6 F 5 one. 33 Cobalt corroles with phosphonic and carboxyl acid pendants functioning as protondonors improve HER activity. 36 Previously, we have used ethoxycarbonyl, 37 nitro, 38 amino, 39 aldehyde and amide pyridyl group 40 substituted cobalt corroles and free-base bis-corrole in the HER.…”
Section: Introductionmentioning
confidence: 99%
“…29 In 2014, Gross 30 firstly used cobalt trispentafluorophenyl corrole in the electrocatalytic HER. Copper, 31 iron 32 and molybdenum 33 corroles have also been applied as HER catalysts. It is found that the substitution of electron withdrawing or donating groups at the meso - or β-position would affect the redox potentials and significantly influence the ability of the complex to act as an electrocatalyst in the reduction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation